SAYING CORRECTLY, WRITING INCORRECTLY: REPRESENTATION OF SETS - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2009)
Sets are one of the important domains in mathematics curricula and may influence students' performance in other topics such as junctions. The aim of the study is to determine difficulties that year 9 Turkish students experience in the sets, frying to reveal their thoughts about sets and their representations. Multi method approaches were used in this study. The data were collected by a diagnostic test of the sets and semi constructed interview.59 high school students participated in this study. Semi constructed interview was conducted by 10 students. The findings showed that students had different type of difficulties in representation of sets; they speak sets correctly but they write sets incorrectly. It is also find that they know what they know but they cannot use their knowledge in different mathematics context.